Sachtlebenia, a new glyptine ichneumonid (Hymenoptera). - Townes, Henry Keith (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There is described a new genus and species of an ichneumonid of the subfamily Banchinae from southeastern China. Nomenclatural Acts Sachtlebenia Townes, 1963 (Ichneumonidae), gen. n. sexmaculata Townes, 1963 (Sachtlebenia), spec. n.